Biogenic sulfuric acid corrosion resistance of new artificial reef concrete. (15th January 2018) - Yang, Yu; Ji, Tao; Lin, Xujian; Chen, Caiyi; Yang, Zhengxian
Highlights: Biogenic sulfuric acid corrosion of concrete was studied. The effect of cement type on the performance of NARC was studied. Biogenic sulfuric acid corrosion of concrete was studied in a simulation device. Biogenic sulfuric acid corrosion resistance of NARC is superior to OPCC. Abstract: Through biogenic sulfuric acid attack on concrete, comparisons between ordinary Portland cement concrete (OPCC) and new artificial reef concrete (NARC) prepared with sulphoaluminate cement, marine sand and sea water were made. Biogenic sulfuric acid corrosion resistance was studied by analyzing the surface and localized morphology, mass loss and compressive strength of both concrete specimens. The corrosion products were investigated by environmental scanning electron microscope (ESEM), X-ray diffraction (XRD) and Fourier-transform infrared (FT-IR). Results showed that the visually apparent corrosion degree and loss rates of mass and compressive strength are higher for OPCC than for NARC following exposure to biogenic sulfuric acid.